In the state administration system of Indonesia: No space for Khilafah! - Handoko, Priyo (HTS teologiese studies, 2021)
This study aims at reducing, and even eliminating, the thoughts of small Muslim groups in Indonesia, which state that the replacement of Pancasila as a Khilafah will raise the Indonesian state to become a developed country. This study uses a normative legal research methodology with two approaches: a historical and a conceptual approach. The historical approach was used to review the history of the implementation of the Khilafah system in Islam and the early history of the emergence of Pancasila as a national government system. Meanwhile, the conceptual approach was used as a road map to examine the Khilafah and Pancasila concepts in the constitutional system. The results of this study revealed that Pancasila represents the Indonesian nation’s ideology, which is in tune with Islamic law, and can answer all the needs of its people. Through Pancasila, the Indonesian people can live in harmony amidst existing pluralism. Therefore, there is no space for ideology other than Pancasila to fill and become the foundation of the Indonesian nation.Contribution: This article attempts to answer Muslim people’s doubts with extremist ideology who want to change Pancasila into Khilafah. No movement seeks to change the Pancasila government system with other government systems.